NEED ANALYSIS OF VIDEO MEDIA DEVELOPMENT PHYSICS LEARNING BASED ON SCIENCE PROCESS SKILLS ON HEAT MATERIAL - Maulida Permata Sari; Dina Marganingsih; Hadma Yuliani (Jambura Physics Journal, 2022)
This study has the objectives of (1) knowing the constraints on students' understanding in learning physics, especially heat material since the Covid-19 pandemic; (2) see the science process skills in students; (3) describe things that need to be developed in learning media in physics learning; and (4) describes the analysis of the needs for developing learning media based on science process skills on the heat material in high school. This type of research uses quantitative and qualitative research methods, by collecting information and data from written test results distributed online to class X students at SMAN 3 Murung. The analysis technique used is descriptive qualitative analysis technique, from data collection conclusions can be obtained (1) There are obstacles experienced by students in understanding the material because the learning system is carried out online. (2) Students have the ability to apply science process skills. (3) Instructional video media need to be developed in physics learning, especially on heat material in order to encourage students to understand the material. (4) A total of 69.20% of students in understanding physics material find it difficult, 92.31% of students have known learning video media, and 92.31% of students stated that science process skills-based learning video media is needed in learning physics, especially heat material, so the media in the form of this learning video needs to be developed.